Assessing the Relationship between Social Media and Sustainable Tourism: A Review - Maitra, Rekha; Tripathi, Ranjeeta; Kumar, Amit; Shukla, Dharna (Nepalese Journal of Hospitality and Tourism Management, 2023)
Achieving sustainability is a primary agenda of developing countries for Vision 2030. On the other hand, technological advancement appears to be a catalyst for achieving those goals. Similarly, the role of social media cannot be ignored while reviewing the impact of tech advancement on our social well-being. This research study evaluates the nexus between different factors of sustainable tourism. It focuses on tourism resources, i.e., natural, artificial, renewable, and non-renewable. Government participation is responsible for optimising economic benefits; while preserving social, cultural, and ecological features. The researcher analyses different social media in India to assess the significance of Responsible/ Sustainable Tourism. This research paper will help the tourists to suggest the various platforms of social media and its importance related to tourism.